Tổng hợp một số dẫn xuất của Lupeol và nghiên cứu hoạt tính kháng vi sinh vật kiểm định - Tuyến, Nguyễn Văn; Hùng, Nguyễn Văn; Chiến, Nguyễn Quyết; Vinh, Nguyễn Đức (Vietnam Journal of Chemistry, 2014)
The lupane triterpenoid lupeol is found in a variety of plants. Its biological activities have attracted a great deal of interests. A number of studies on the antiinflammatory, antimycobacterial, antimalarial and anticancer activities of this compound and its derivatives have been reported. Based on our knowledge, there have not been any reports on the antimicrobial activity of lupeol and its derivatives. In order to investigate the relationship between the chemical structure and  antimicrobial activities, several derivatives of lupeol, such as lupeol acetate, lupeol isobutyrate, lupeol benzoate and lupeol cinnamate were synthesized, and the antibacterial and antifungal effects of these derivatives were examined. It was found  that these  derivatives possessed only weak antimicrobial activities, and that the above acylation of the OH group at C-3 did not lead to  an improvement of the  antibacterial and anti-fungal activities.